Enhancement of Selective Mapping Technique for Peak-To-Average Power Ratio Reduction in OFDM using Normalized Hilbert Matrix - Tekanyi, A. M. S.; Yarima, H. I.; Sani, S. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Orthogonal Frequency Division Multiplexing (OFDM) is good multicarrier transmission system used for broadband wireless communication systems owing to it is numerous benefits such as high bandwidth efficiency, high transmission rate, and robustness against multi path problem. However, one of the hitches of OFDM high Peak-to-Average Power Ratio (PAPR) of the transmitted signal, which results in signal distortion and reduced power amplifier efficiency. Selective Mapping (SLM) is attractive distortion less method for PAPR reduction. The performance of this technique in reducing the PAPR is largely affected by the magnitude of phase rotation vectors. It also requires to transmit the selected phase rotation vectors that produce the signal with the lowest PAPR to the receiver end for the recovery of the original data. In this paper, two normalization procedures in conjunction with the Hilbert matrix are used to obtain phase rotation vectors for the SLM technique to further reduce the PAPR value. The reduction of PAPR is desirable in order to have a better power efficiency of the amplifier. The simulation results demonstrated that the enhanced SLM technique using normalized Hilbert matrix achieved a better PAPR reduction compared to SLM using Hilbert matrix without normalization with 14.0%, and 14.0% percentage improvement. Another benefit of this method is that the matrix can be generated at the receiver end to obtain the data signal, thus eliminating the transmission of side information with the original data.